(untitled) (Marketing Jurnali, 2026)
The study examined the current dynamics, structural features, and development prospects of India–Uzbekistan trade relations through 2030. It found sustained growth in bilateral trade and an expanding role for pharmaceuticals, services, investment, uranium, and strategic minerals. The analysis showed that the bilateral investment treaty, Uzbekistan’s WTO accession process, and market-access agreements strengthened the institutional foundation of cooperation. Although transport and logistics constraints remained, services, aviation, and digital linkages supported continued trade expansion. The study concluded that diversifying bilateral trade, expanding mutual investment, and improving trade balance contributed to a more resilient strategic partnership and created broader opportunities for long-term economic cooperation between the two countries.